Chemical constituents from the fruits of Vitex trifolia L. (Verbenaceae) and their chemotaxonomic significance. (August 2021) - Djimabi, Komi; Li, Bing; Chen, Xiao-Han; Su, Pan-Jie; Liu, Xu; Wang, Ru-Yue; Qi, Feng-Ming; Wang, Mei-Jie; Fei, Dong-Qing; Zhang, Zhan-Xin
Abstract: One new labdane-type diterpenoid (1 ) named viterotulin D, along with twenty-three known compounds, including fourteen diterpenoids (2 –15 ), one monoterpenoid (16 ), three steroids (17 –19 ), one flavonoid (20 ), and four phenols (21 –24 ) were isolated from the fruits of Vitex trifolia L. The structures of these compounds were identified based on spectroscopic data interpretation and comparison with previously reported values in the literature. This is the first report on the isolation of compounds (1, 6, 14, 15, 17, and 22 ) and (2, 9, and 10 ) from the family Verbenaceae and Vitex trifolia, respectively. The chemotaxonomic significant of the isolates was also discussed. Graphical abstract: Image 1 Highlights: One new labdane-type diterpenoid and twenty-three known compounds were isolated from the fruits of Vitex trifolia. Compounds 2, 9, and 10 were firstly found from Vitex trifolia. Compounds 1, 6, 14, 15, 17, and 22 were firstly found from the family Verbenaceae. Diterpenoids could be obviously considered as chemotaxonomic markers for the genus Vitex.